Pengaruh Pemasaran Event terhadap Citra Merek Minuman Isotonik Mizonedi Surabaya - Muhammad Hirza Sukoco (Universitas Negeri Surabaya, 2018)
Event marketing was previously consideredas a complementary formarketing communications. Currently event marketing is increasingly recognized as one of the effective ways to build brand image of a company. one of the companies that use event marketing as one of the strategies is Mizone. therefore, this study aims to investigate the influence of event marketing to the brand image. Limitation of the studyis the respondents who attend the event or who purchase the product when the event took place. The samples were used as much as 210 people. using purposive sampling technique. The research instrument that used was a questionnaire, and simple linear regression analysis. This study shows there is positive effect between event marketing to brand image Mizone isotonic water